2000
DOI: 10.1046/j.1523-1755.2000.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nutritional status and the glomerular filtration rate: Results from the MDRD Study

Abstract: These cross-sectional findings suggest that in patients with chronic renal disease, dietary protein and energy intakes and serum and anthropometric measures of protein-energy nutritional status progressively decline as the GFR decreases. The reduced protein and energy intakes, as GFR falls, may contribute to the decline in many of the nutritional measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
215
4
16

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(251 citation statements)
references
References 41 publications
16
215
4
16
Order By: Relevance
“…In a prospective study with minimal dietary interventions, Ikizler et al (1995) demonstrated that the decline in renal function was accompanied by a decrease in protein intake. In the baseline period of the Modification of Diet in Renal Disease (MDRD) study, a cross-sectional analysis showed a direct correlation between glomerular filtration rate and nutritional status that is, patients with low glomerular filtration rate had lower protein and energy intake, and decreased anthropometric parameters (Kopple et al, 2000). Some findings were similarly observed in the MDRD study and in the present one; however, there were differences comparing the populations studied.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In a prospective study with minimal dietary interventions, Ikizler et al (1995) demonstrated that the decline in renal function was accompanied by a decrease in protein intake. In the baseline period of the Modification of Diet in Renal Disease (MDRD) study, a cross-sectional analysis showed a direct correlation between glomerular filtration rate and nutritional status that is, patients with low glomerular filtration rate had lower protein and energy intake, and decreased anthropometric parameters (Kopple et al, 2000). Some findings were similarly observed in the MDRD study and in the present one; however, there were differences comparing the populations studied.…”
Section: Discussionsupporting
confidence: 69%
“…This finding suggests that factors related to the loss of renal function other than anorexia are important to the deterioration of the nutritional condition. These results differ somewhat from those found in the MDRD study, where the relation between nutritional parameters and glomerular filtration rate were markedly reduced after controlling for protein and energy intake (Kopple et al, 2000). Malnutrition at the initiation of dialysis has been implicated in poor outcome and higher morbidity and mortality risk (Hakim & Lazarus, 1995;Holland & Lam, 2000).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In nontransplant native renal disease, this classification scheme is appropriate as the prevalence of complications increases significantly as the GFR declines (1). Hypertension (2), anemia (3) and hypoalbuminemia (4), to name a few, are all more prevalent at lower levels of GFR.…”
Section: Introductionmentioning
confidence: 99%